Evaluation of endoscopic secondary prophylaxis in children and adolescents with esophageal varices - PIMENTA,Júlio Rocha (2017)
ABSTRACT BACKGROUND Bleeding of esophageal varices is the main cause of morbidity and mortality in children and adults with portal hypertension and there are few studies involving secondary prophylaxis in children and adolescents. OBJECTIVE To evaluate the efficacy of endoscopic secondary prophylaxis in prevention of upper gastrointestinal bleeding in children and adolescents with esophageal varices. METHODS This is a prospective analysis of 85 patients less than 18 years of age with or without cirrhosis, with portal hypertension. Participants underwent endoscopic secondary prophylaxis with sclerotherapy or band ligation. Eradication of varices, incidence of rebleeding, number of endoscopic sessions required for eradication, incidence of developing gastric fundus varices and portal hypertensive gastropathy were evaluated. RESULTS Band ligation was performed in 34 (40%) patients and sclerotherapy in 51 (60%) patients. Esophageal varices were eradicated in 81.2%, after a median of four endoscopic sessions. Varices relapsed in 38 (55.1%) patients. Thirty-six (42.3%) patients experienced rebleeding, and it was more prevalent in the group that received sclerotherapy. Gastric varices and portal hypertensive gastropathy developed in 38.7% and 57.9% of patients, respectively. Patients undergoing band ligation showed lower rebleeding rates (26.5% vs 52.9%) and fewer sessions required for eradication of esophageal varices (3.5 vs 5). CONCLUSION Secondary prophylaxis was effective in eradicating esophageal varices and controlling new upper gastrointestinal bleeding episodes due to the rupture of esophageal varices. Band ligation seems that resulted in lower rebleeding rates and fewer sessions required to eradicate varices than did sclerotherapy.